ACTUALIZATION DEFINITIONS AND THEORETICAL JUSTIFICATION DISTRIBUTION RATIO OF OIL AND GAS ROYALTIES UNDER DECENTRALIZATION - Horal, L. T.; Perevozova, I. V.; Shyiko , V. I. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The need to elaborate the factor of redistribution of rent payments between different levels of budgets has been updated. The purpose of the article is to determine the functional manifestations of rent payments in the modern institutional environment, formed in the context of decentralization, to analyze and evaluate the actual income of rent payments to the budget, taking into account their retrospective, to identify the main directions of improving the redistribution of rent payments between budgets. While writing the article, general scientific methods of cognition were used: the combination of dialectics and historicism - during the study of the evolution of the distribution the rent payments; methods of scientific abstraction, induction and deduction, as well as other methods of knowledge of socio-economic phenomena, objects and processes for formulation scientific regulations and clarification the definitions rent payments; quantitative and qualitative comparison, analysis and synthesis, graphical methods of research, economic and statistical methods of information collection and processing for statistical analysis and estimation of rent receipts to the budget. A complex of researches the functional manifestations of rent payments and a demarcated functional field of rent is conducted. The mechanisms, principles and tools for charging and leasing rent payments in the oil and gas complex in the normative legislative and regulatory documents of Ukraine were analyzed; a vision of the distribution of payments between the state and local budgets is formed based on the nature of their functional manifestations. The retrospective of rent payments to the State Budget was evaluated.. Based on the conducted researches has been developed the economic-mathematical model of the coefficient of redistribution rent payments with the account of their functional nature. The basic directions of improvement of redistribution improvement of rent payments between budgets are defined. In order to increase the volume of receipts of rent payments to the budgets, proposed the ways and directions of intensification of hydrocarbon production by improving the legislative and normative base of Ukraine for increase the investment attractiveness of the industry. Differentiation of rent payments is made depending on the factors that have the greatest influence on the formation of the cost of oil production to stimulate entrepreneurial activity, the directions of improvement of accounting of geological prospecting and extraction works are formed, the priority conditions for drilling production are formed.